2020
DOI: 10.5539/mas.v14n3p75
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cyber Governance in Reducing the Risk of Cloud Accounting in Jordanian Commercial Banks - from the Perspective of Jordanian Auditing Firms

Abstract: The objective of this study is identifying the impact of cyber governance on reducing the risk of cloud accounting in the Jordanian commercial banks. To achieve the objectives of this study, the descriptive and analytical approach was used; the study community is composed of external legal accountants who practices auditing in Jordan, (477) of them are practicing external auditing at the end of (2018) according to the statistics of the Jordanian association of certified public accountants (JACPA). Due to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In addition to the need to adopt cyber governance as a fundamental reference to banking policies, the requirements of special departments for human resource management within the bank that will have a leading intellectual orientation to deal with modern trends in cyber governance are also described (Ali et al. 2020 ).…”
Section: Findings and Reviewmentioning
confidence: 99%
“…In addition to the need to adopt cyber governance as a fundamental reference to banking policies, the requirements of special departments for human resource management within the bank that will have a leading intellectual orientation to deal with modern trends in cyber governance are also described (Ali et al. 2020 ).…”
Section: Findings and Reviewmentioning
confidence: 99%
“…CA also has the characteristics of depends on the request services, service flexibility, network access, resource sharing, flexible service, and measured service (Moudud-Ul-Huq et al, 2020). In the traditional AIS, all devices and applications are located within the company (Ali et al, 2020). However, when companies use CA services, the cloud service providers own, manage and control the CA infrastructure (Khanom, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shkurti and Muça (2014) found that data security and compatibility with current systems as well as information accuracy are among the most prominent risks of using CA. Ali et al (2020) believes that security and privacy risks are among the most prominent risks of using CA. Corkern et al (2015) suggest that companies may use CA when addressing reliability and security issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations